2010
DOI: 10.1105/tpc.110.076182
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Chromatin Assembly Factor 1 Induces Shortening of Telomeres and Loss of 45S rDNA inArabidopsis thaliana   

Abstract: Chromatin Assembly Factor 1 (CAF1) is a three-subunit H3/H4 histone chaperone responsible for replication-dependent nucleosome assembly. It is composed of CAC 1-3 in yeast; p155, p60, and p48 in humans; and FASCIATA1 (FAS1), FAS2, and MULTICOPY SUPPRESSOR OF IRA1 in Arabidopsis thaliana. We report that disruption of CAF1 function by fas mutations in Arabidopsis results in telomere shortening and loss of 45S rDNA, while other repetitive sequences (5S rDNA, centromeric 180-bp repeat, CACTA, and Athila) are unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
156
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(169 citation statements)
references
References 116 publications
(135 reference statements)
13
156
0
Order By: Relevance
“…Telomeres protect the chromosome ends from unscheduled DNA repair reactions and degradation. In agreement with a previous report (Mozgová et al, 2010), we found that telomeres were shortened in fas2-4 ( Figure 5B). By contrast, telomere length was comparable between nrp1-1 nrp2-1 and Col and between nrp1-1 nrp2-1 fas2-4 and fas2-4 ( Figure 5B), indicating that depletion of NRP1 and NRP2 does not affect telomere length maintenance and cannot attenuate the telomere shortening caused by CAF-1 depletion.…”
Section: Nrp1 and Nrp2 Depletion Suppresses The Hyperrecombinogenic Psupporting
confidence: 94%
See 1 more Smart Citation
“…Telomeres protect the chromosome ends from unscheduled DNA repair reactions and degradation. In agreement with a previous report (Mozgová et al, 2010), we found that telomeres were shortened in fas2-4 ( Figure 5B). By contrast, telomere length was comparable between nrp1-1 nrp2-1 and Col and between nrp1-1 nrp2-1 fas2-4 and fas2-4 ( Figure 5B), indicating that depletion of NRP1 and NRP2 does not affect telomere length maintenance and cannot attenuate the telomere shortening caused by CAF-1 depletion.…”
Section: Nrp1 and Nrp2 Depletion Suppresses The Hyperrecombinogenic Psupporting
confidence: 94%
“…NRPs also contrast with CAF-1 in telomere length control. While telomeres are shortened in the fas mutants (Mozgová et al, 2010; this study), depletion of NRP1 and NRP2 does not affect telomere length. Telomeres contain tandem short DNA sequence repeats, thus representing potential substrates for HR.…”
Section: Discussionsupporting
confidence: 43%
“…Arabidopsis thaliana FASCIATA 1 (FAS1) and FAS2 are subunits of chromatin assembly factor 1 (CAF1), a histone chaperone implicated in replication-dependent deposition of histones H3 and H4 (Ramirez-Parra and Gutierrez 2007). In fas1 or fas2 mutants, 45S rRNA genes are lost (Mozgova et al 2010), as shown by DNA-FISH (Fig. 3A) or quantitative PCR (qPCR) (Fig.…”
Section: Variant-specific Silencing Is Disrupted When Rrna Gene Copy mentioning
confidence: 77%
“…DNA-FISH and qPCR analyses of fas mutants were performed as previously described (Mozgova et al 2010) using 18S rRNA gene primers CTAGAGCTAATACGTGCAACAAAC (forward) and GAATCGAACCC TAATTCTCCG (reverse) and UBIQUITIN 10 (UBQ10) control primers AACGGGAAAGACGATTAC (forward) and ACAAGATGAAGGGTG GAC (reverse). DNA-FISH, RNA-FISH, and protein immunolocalization of Flag-tagged proteins were performed as described previously (Pontes et al 2003.…”
Section: Dna-fish and Qpcrmentioning
confidence: 99%
“…30 This homeostasis is compromised in the CAF-1 mutants fasciata, where rDNA copies are progressively lost and the originally inactive rRNA gene copies translocate into the nucleolus and are expressed. 30,31 Jiri Fajkus (Brno, Czech Republic) showed that the reintroduction of a wild-type FAS allele into fas mutant plants that have been inbred for several generations can lead to reversion of the rRNA gene copy-number but causes major changes in the bulk variant composition, their transcriptional state and nuclear localization, suggesting reprogramming and establishment of a novel epigenetic equilibrium at the nucleolus organizer regions in these plants.…”
Section: Organized Genome In An Organized Nucleusmentioning
confidence: 99%